Robust stabilisation for constrained discrete‐time switched positive linear systems with uncertainties. Issue 17 (1st November 2015) - Liu, Jinjin; Zhang, Kanjian; Pang, Guochen; Wei, Haikun
Abstract : Robust stabilisation problem of discrete‐time switched linear systems with bounds on the controls and states is investigated in this study. Firstly, the controller synthesis for systems with interval uncertainties which guarantees positivity and stability of the closed‐loop system is studied. These results are then extended to the systems with polytopic uncertainties. All the conditions are formulated in terms of linear feasibility. Finally, numerical examples illustrate the effectiveness of the proposed methods.